2019
DOI: 10.1002/etc.4582
|View full text |Cite
|
Sign up to set email alerts
|

An Early–Life Stage Alternative Testing Strategy for Assessing the Impacts of Environmental Chemicals in Birds

Abstract: Early-life stage (ELS) toxicity tests are recognized as an advancement over current testing methodologies in terms of cost, animal use, and biological relevance. However, standardized ELS tests are not presently available for some vertebrate taxa, including birds. The present study describes a Japanese quail (Coturnix japonica) ELS test that is a promising candidate for standardization and applies it to test 8 environmental chemicals (ethinylestradiol, benzo[a]pyrene, chlorpyrifos, fluoxetine, lead(II)nitrate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(79 citation statements)
references
References 59 publications
(101 reference statements)
6
70
2
Order By: Relevance
“…; reported purity ≥95%) were included in the double‐crested cormorant egg injection studies: BaP, chlorpyrifos, FLX, and EE2. Dimethyl sulfoxide (DMSO; Sigma‐Aldrich) was the solvent selected to prepare stock and working solutions; a detailed justification for selecting DMSO for early‐life stage avian egg injection studies can be found in Farhat et al (2020). Based on the Japanese quail early‐life stage toxicity study by Farhat et al (2020), we selected a high dose that we assumed would not exceed 20% lethality of the exposed organisms.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…; reported purity ≥95%) were included in the double‐crested cormorant egg injection studies: BaP, chlorpyrifos, FLX, and EE2. Dimethyl sulfoxide (DMSO; Sigma‐Aldrich) was the solvent selected to prepare stock and working solutions; a detailed justification for selecting DMSO for early‐life stage avian egg injection studies can be found in Farhat et al (2020). Based on the Japanese quail early‐life stage toxicity study by Farhat et al (2020), we selected a high dose that we assumed would not exceed 20% lethality of the exposed organisms.…”
Section: Methodsmentioning
confidence: 99%
“…Dimethyl sulfoxide (DMSO; Sigma‐Aldrich) was the solvent selected to prepare stock and working solutions; a detailed justification for selecting DMSO for early‐life stage avian egg injection studies can be found in Farhat et al (2020). Based on the Japanese quail early‐life stage toxicity study by Farhat et al (2020), we selected a high dose that we assumed would not exceed 20% lethality of the exposed organisms. Wherever possible, nominal concentrations were chosen to match our previous study, although actual concentrations may differ.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations